Eco-affecting Reporting Practices of Publicly Traded Engineering Companies in Bangladesh - Islam, S. M. Faridul; Hossain, Syed Zabid (Journal of Environmental Accounting and Management, 2026)
Based on corporate characteristics, this study explored the extent and nature of eco-affecting information reporting practices of publicly listed engineering companies in the context of an emerging economy. Data collected from annual reports of the purposively selected companies in the 'Engineering Sector' of Dhaka Stock Exchange (DSE) applying a self-developed reporting index consisted of 38 reporting items. The study found that the average eco-affecting information disclosed by the sample firms was only 12.81% of the disclosure checklist, and that was descriptive in nature. The highest disclosed issue was environmental concern and policies (25%), while the lowest was environmental performance (3.81%). The most revealing is that 13.33% of the sample companies did not disclose any eco-affecting information in their annual reports. The study found that firms' visibility proxied by their total assets showed a significant positive effect on the extent of eco-affecting information disclosure. Contrarily, business experience proxied by firms' age showed a negative impact on eco-affecting information disclosure. Other explanatory variables, viz., firm category, leverage, profitability, and ownership stake of the state have an insignificant effect on eco-affecting information disclosure. The findings of this paper will help the policymakers and regulators frame environmental policies and regulations -considering the potential impact of different corporate characteristics-related explanatory variables on environmental reporting. The study is unique as the sample has accepted a specific manufacturing industry instead of mixing industry categories. The study considered 'Company Category' as an explanatory variable for the first time. Besides, the study has included two new disclosure items, viz. environmental slogan/ dialogue and rainwater harvesting (RWH), which have been missing in prior literature.